“Stay with your words”: Indigenous youth, local policy, and the work of language fortification - Sumida Huaman, Elizabeth; Martin, Nathan D.; Chosa, Carnell T. (Education Policy Analysis Archives, 2016)
This article focuses on the work of cultural and language maintenance and fortification with Indigenous youth populations. Here, the idea of work represents two strands of thought: first, research that is partnered with Indigenous youth-serving institutions and that prioritizes Indigenous youth perspectives; and second, the work of cultural and linguistic engagement that is often taken for granted as part of the sociocultural fabric of Indigenous communities where youth are active participants. By highlighting a study with Pueblo Indian youth in the southwestern United States, we aim to build on the counter-narrative frameworks of other educational scholars and community-based researchers in order to offer alternative approaches towards understanding how Indigenous youth can and do participate in representing themselves as cultural and language agents of change. Arriving at this realization requires several key steps, including deconstructing dominant assumptions, holding ourselves accountable for interrogating and revisiting our own biases, and ultimately committing to long-term research and support with Indigenous youth. As such, we offer empirical evidence that contradicts universal discourse of Indigenous peoples and youth as victims at risk. Instead, we focus on the ways in which Indigenous youth demonstrate both tentative and bold fortification of key elements in their Indigenous identities and illustrate promise in contribution to multiple levels of policy development to address their communities’ most urgent needs and goals.